The Utility of MRI in the Diagnosis of Takayasu Arteritis - Marian Gaballah; Rachelle Goldfisher; John B. Amodio (Hindawi Limited, 2017)
Takayasu Arteritis (TA) is an inflammatory disorder involving the thoracoabdominal aorta and its branches and the pulmonary arteries, with eventual vascular stenosis, occlusion, or aneurysm formation. Conventional angiography has been the reference imaging standard for diagnosis of TA. The purpose of this case report is to demonstrate the utility of MR imaging and MR angiography in the diagnosis of Takayasu Arteritis in a pediatric patient. The patient is a 15-year-old female patient presenting with anemia, hypertension, and acute kidney injury. Initial chest CT demonstrated ectasia of the ascending and focal stenosis of the descending thoracic aorta, prompting further evaluation with MRI and MRA. MRI/MRA demonstrated mural thickening with luminal stenosis of the aorta and aortic branch vessels. These imaging findings were suggestive of a large vessel arteritis and along with the clinical presentation and laboratory abnormalities the diagnosis of Takayasu Arteritis was suggested. Several case series in adults have described the cross-sectional findings of TA. However, this case report demonstrates the utility of MRI/MRA in the evaluation of TA in children and in the course of follow-up, as it provides a noninvasive method for evaluating a child without ionizing radiation or iodinated contrast.